Utility of MIB-1 and estrogen and progesterone receptor in distinguishing between endometrial stromal sarcomas and endometrial stromal nodules, highly cellular leiomyomas. Issue 2 (1st February 2005) - Kir, G.; Cetiner, H.; Karateke, A.; Gurbuz, A.; Bulbul, D.
Abstract : It is difficult to differentiate between an endometrial stromal nodule (ESN) and endometrial stromal sarcoma (ESS) in curettage specimen, and the recommended therapy of endometrial stromal neoplasm is hysterectomy. If we could discriminate ESS from ESN in curettage specimens, there would be an opportunity to treat ESN by local excision rather than by hysterectomy. We analyzed MIB-1 and estrogen and progesterone receptor (ER/PR) expression in a retrospective series of 8 ESSs, 7 ESNs, and 17 highly cellular leiomyomas obtained from hysterectomy specimens. ESSs expressed MIB-1 more frequently than ESNs ( P < 0.05), and ESSs had a tendency to express ER less frequently than ESNs ( P = 0.08). We observed that in spite of showing MIB-1 expression to some extent, highly cellular leiomyomas usually could not reach ESSs' level and frequency of MIB-1 expression in the current study. Although MIB-1 and ER appear to be promising markers in the differential diagnosis of ESSs, a larger study would be necesary to confirm their validity.